The Effect Of Information Flow, Information Adequacy And Interaction Supportiveness On Organizational Commitment With Job Engagement As An Intervening - Fikri Budi Berliawan; Nursaid Nursaid; Riyanto Setiawan; Budi Santoso (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to explore how information flow, information adequacy, interaction supportiveness, and job engagement impact organizational commitment. A descriptive and verificative approach was employed to examine the relationship between information flow, information adequacy, and interaction supportiveness on organizational commitment, with job engagement as the intervening variable. Data were collected through questionnaires, observations, and literature reviews involving a sample of 250 employees selected using accidental sampling. Hypothesis testing was conducted using path analysis with the assistance of SmartPLS software. The results show that information adequacy and job engagement have a direct influence on organizational commitment among Generation Y employees in the Surabaya–Sidoarjo area, while information flow and interaction supportiveness do not have a direct effect. However, the three variables (information flow, information adequacy, and interaction supportiveness) were found to significantly affect job engagement. Furthermore, job engagement was proven to mediate the effect of information flow, information adequacy, and interaction supportiveness on organizational commitment.